2004
DOI: 10.1073/pnas.0307529101
|View full text |Cite
|
Sign up to set email alerts
|

Two feeding-induced proteins from the male gonad trigger engorgement of the female tickAmblyomma hebraeum

Abstract: Most female ixodid ticks, once mated, feed to repletion within 6 -10 days. Previous studies indicate that an engorgement factor (EF), passed to the female during copulation, may be the stimulus for engorgement. Here, we show that extracts of the testis͞vas deferens of fed (but not unfed) male Amblyomma hebraeum contain EF bioactivity when injected into the hemocoel of feeding virgins. We have produced recombinant proteins (recproteins) from 28 feeding-induced genes in the male gonad and have identified a recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 26 publications
(16 reference statements)
4
55
2
1
Order By: Relevance
“…It is well known that ticks are able to reattach following involuntary detachment from hosts (Gregson, 1960; Jaworski et al ., 1992; Wang, Henbest & Nuttall, 1999; Weiss & Kaufman, 2004). Cement production allows superficial attachment of ticks to the host and it might be speculated that this is advantageous during grooming by the host to remove the parasite.…”
Section: Biological Significance and Functions Of The Cementmentioning
confidence: 99%
“…It is well known that ticks are able to reattach following involuntary detachment from hosts (Gregson, 1960; Jaworski et al ., 1992; Wang, Henbest & Nuttall, 1999; Weiss & Kaufman, 2004). Cement production allows superficial attachment of ticks to the host and it might be speculated that this is advantageous during grooming by the host to remove the parasite.…”
Section: Biological Significance and Functions Of The Cementmentioning
confidence: 99%
“…These proteins include: (1) simple peptides, including a "sex peptide" (Acp70A) that induces sexual refractoriness, increases the rate of egg production, and changes the feeding behavior and longevity of female Drosophila (Chapman et al, 2003;Liu and Kubli, 2003;Wigby and Chapman, 2005;Carvalho et al, 2006); (2) "prohormone-like" peptides, one of which (ovulin/Acp26Aa) stimulates ovulation (Heifetz et al, 2000); (3) large glycoproteins which are important for sperm storage (Neubaum and Wolfner, 1999) and other sperm-binding proteins; and (4) proteolysis regulators (Mueller et al, 2004;Ravi Ram et al, 2006;Mueller et al, 2007). Proteins synthesized in the male reproductive tract also have been found to play a role in regulating female post-mating physiology in a broad representation of other arthropods, including muscoid flies (Nelson et al, 1969), moths (Park et al, 1998), and ticks (Weiss and Kaufman, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Antitick vaccines have been developed based on the molecular cloning, characterization and analysis of tick molecules that play an important role in tick physiology. Weiss and Kaufman (2004) reported that the transfer of voraxin-a and voraxin-b via copulation is essential for female engorgement and oviposition in A. hebraeum. He also speculated that male factor (MF) from male gonad of A. hebaerum, which can hasten the onset of salivary gland degeneration (Lomas and Kaufman 1992) and engorgement factor (EF) from D. variabilis, which are produced by the male and promotes female feeding to repletion (Pappas and Oliver 1972) are the same substance because both factors are found in testis of fed males.…”
Section: Discussionmentioning
confidence: 99%
“…Weiss and Kaufman (2004) cloned male testis/vas deferens-derived 'voraxin' from Amblyomma hebraeum and first showed that injection of recombinant voraxin into virgin females stimulates blood feeding to engorge. In addition, mean tick weight was significantly reduced and 75 % of the mated female ticks tested did not engorge at all on immunized animals.…”
Section: Introductionmentioning
confidence: 99%